2020
DOI: 10.1101/2020.09.18.302901
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2 Nsp1 suppresses host but not viral translation through a bipartite mechanism

Abstract: SUMMARYThe Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) is a highly contagious virus that underlies the current COVID-19 pandemic. SARS-CoV-2 is thought to disable various features of host immunity and cellular defense. The SARS-CoV-2 nonstructural protein 1 (Nsp1) is known to inhibit host protein translation and could be a target for antiviral therapy against COVID-19. However, how SARS-CoV-2 circumvents this translational blockage for the production of its own proteins is an open question. He… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
91
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(98 citation statements)
references
References 37 publications
(51 reference statements)
7
91
0
Order By: Relevance
“…By their nature, deep sequencing measurements provide relative values but not absolute quantification of RNA and translation levels. Since SARS-CoV-2 encoded protein, NSP1, was recently shown to interfere with translation by blocking the mRNA entry channel of ribosomes [25][26][27][28] , and since the extent to which SARS-CoV-2 interferes with the overall levels of cellular mRNA was not assessed, we next examined if SARS-CoV-2 infection affects global translation and RNA levels. To quantify absolute translation levels, we measured nascent protein synthesis levels using an analogue of puromycin, O-Propargyl Puromycin (OPP), which incorporates into elongating polypeptide chains 34 .…”
Section: Results: Simultaneous Monitoring Of Rna Levels and Translatimentioning
confidence: 99%
See 3 more Smart Citations
“…By their nature, deep sequencing measurements provide relative values but not absolute quantification of RNA and translation levels. Since SARS-CoV-2 encoded protein, NSP1, was recently shown to interfere with translation by blocking the mRNA entry channel of ribosomes [25][26][27][28] , and since the extent to which SARS-CoV-2 interferes with the overall levels of cellular mRNA was not assessed, we next examined if SARS-CoV-2 infection affects global translation and RNA levels. To quantify absolute translation levels, we measured nascent protein synthesis levels using an analogue of puromycin, O-Propargyl Puromycin (OPP), which incorporates into elongating polypeptide chains 34 .…”
Section: Results: Simultaneous Monitoring Of Rna Levels and Translatimentioning
confidence: 99%
“…In CoVs, the most prominent and well characterized cellular shutoff protein is NSP1 23 . So far, studies on SARS-CoV-2 NSP1 demonstrated it restricts translation by directly binding to the ribosome 40S subunit [25][26][27][28] , thereby globally inhibiting translation initiation. For SARS-CoV, on top of this translation effect, NSP1 interactions with the 40S was also shown to induce cleavage of translated cellular mRNAs, thereby accelerating their turnover their translation we compiled a list of 14 long non-coding RNAs (lncRNAs) that localize to the cytoplasm and are well expressed in our data but, as expected, poorly translated ( Figure S4B).…”
Section: Cellular Mrnas Are Degraded During Sars-cov-2 Infectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, it has been shown that the N-terminal domain of SARS-CoV-2 NSP1 is required for viral translation by NSP1-bound ribosomes (Shi et al, 2020). The linker length between the N-and C-terminal domains is critical for viral translation .…”
Section: Introductionmentioning
confidence: 99%